Analisis Pengaruh Penggunaan Visual Basic Application Terhadap Minat Belajar Matematika Siswa SD pada Materi Bilangan Prima - Ernawati; Nurhayati, Leni; Chotimah, Siti (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2020)
The purpose of this study is to describe the interest in learning mathematics for fifth grade elementary school students on prime number material assisted by ICT learning media, namely Visual Basic Application (VBA) Excel. The research method uses qualitative descriptive research. The subjects of this study were 5th grade students of Madrasah Ibtidaiyah (MI) II Celak which consisted of 26 students. The instrument was given in the form of a questionnaire for students' interest in learning consisting of 20 statements, with 10 positive statements each and 10 negative statements from five indicators, 1). Feelings of pleasure, 2). Student interests, 3). Student involvement, 4). Diligent in studying and diligent in doing math tasks, 5). Diligent and disciplined in learning and having a study schedule. Based on the results of data analysis, it was found that learning mathematics using VBA media can increase student learning interest. This is shown by the percentage of each indicator of student interest in learning. The highest indicator is the feeling of pleasure and interest of students in learning mathematics, each getting 87.02% and 89.18% which shows that students' interest in learning mathematics is very high.